Preparation of Mint essential oil and its encapsulation using Sodium Alginate, Starch and Maltodextrin Polymers - Gholam Reza Najafi; Homa Ahmadi; Mahboubeh A. Sharif (بیولوژی کاربردی, 2019)
Because the role of essential oils and aromatic substances in plants is lost due to chemical evaporation or chemical instability over time, Many methods have been used to increase the stability and durability of essential oils, and encapsulation is one of the most important ones. In this study, micro or nanocapsules containing mint essential oil were prepared by coacervation and freeze drying methods using various polymers such as sodium alginate, starch and malto dextrin. Initially, with different weighing of each of the polymers, solutions were prepared with deionized water to achieve the best concentration. The ultrasound homogenizer was then used to homogenize, and the mint essence was gradually added to the homogeneous solution. The capsules were prepared immediately after preparing homogeneous polymer and essential oil mixtures. After that, the capsules were evaluated by scanning electron microscopy(SEM). The type of polymer, polymer concentration and mixing speed are among the factors affecting the type of capsule and how the mint essence is released.